Low-dose esketamine with sufentanil for postcesarean analgesia in women with gestational diabetes mellitus: a prospective, randomized, double-blind study - Han, Tao; Chen, Qin; Huang, Jie; Zhang, Jie; Li, Aiyuan; Xu, Wei; Peng, Zheming; Li, Zhen; Chen, Liang (Frontiers in Endocrinology, 2023)
Background: Pregnant women with gestational diabetes mellitus (GDM) require more analgesics after cesarean delivery than those who do not have GDM. Uncontrolled pain following cesarean delivery is a major problem in women with GDM. We investigate the efficacy of low-dose esketamine combined with sufentanil intravenous patient-controlled analgesia (PCA)for postcesarean analgesia in women with GDM. METHODS: One hundred forty pregnant women with GDM were enrolled participate in this randomized controlled trial and were randomized into two groups (70 in each group). The esketamine (S) group was given esketamine +sufentanil + ondansetron, and the control (C) group was given sufentanil +ondansetron. The primary outcome is sufentanil consumption at 24 hours postoperatively, the secondary outcomes are sufentanil consumption at 6 hours postoperatively, pain scores at 6, 24 and 48 hours postoperatively. RESULTS: Compared with group C, group S had significantly lower sufentanil consumption at 6 and 24 hours postoperatively ( P= 0.049 and P<0.001), significantly lower activities VAS(pain during activities)scores at 6 hours postoperatively, rest and activities VAS (pain at rest and pain during activities)scores at 24 hours postoperatively, and activities.VAS scores at 48 hours postoperatively( P=0.022, P =0.002, P=0.001 and P=0.007). Compared to group C, the time to bowel function return was significantly shorter in group S. There was no significant difference in rest VAS (pain at rest) scores at 6 and 48 hours postoperatively (P>0.05). The time to first lactation was not significantly different between the two groups (P>0.05). There was no significant difference in neonatal neurobehavioral scores between the two groups (P>0.05). CONCLUSION: Compared to sufentanil PCA, adding low dose of esketamine significantly reduced the consumption of sufentanil while providing equally effective post cesarean analgesia in the patients with gestational diabetes.